PROMIS Scores for Plantar Fasciitis Before and After Gastrocnemius Recession. (May 2023) - Sanchez, Thomas; Sankey, Turner; Schick, Sam; Arthur, Rodney; Young, Matt; Underwood, Meghan; Harrelson, Whitt; Shah, Ashish
Background: There has been an established relationship between increased loading on the Achilles tendon and tension on the plantar fascia. This supports the idea that either tight gastrocnemius and soleus muscles or contractures of the Achilles tendon are risk factors for plantar fasciitis. Gastrocnemius recession has gained popularity as a viable surgical intervention for cases of chronic plantar fasciitis due to isolated gastrocnemius contracture. To our knowledge, this is the first study to investigate Patient-Reported Outcome Measurement Information Systems (PROMIS) scores in patients with plantar fasciitis before and after gastrocnemius recession. Methods: The Electronic Medical Record was queried for medical record numbers associated with Current Procedural Terminology code 27687 (gastrocnemius recession). Our study included all patients with a preoperative diagnosis of chronic plantar fasciitis with treatment via isolated gastrocnemius recession with 1-year minimum follow-up. Forty-one patients were included in our study. Patient variables were collected via chart review. Preoperative and postoperative PROMIS scores were collected in the clinic. Results: We followed up 41 patients with a median age of 48 years (interquartile range [IQR] 38-55) and median body mass index of 29.02 (IQR 29.02-38.74) for 1 year post surgery. Preoperative and postoperative PROMIS scores improved for physical function from 39.3 to 44.5 ( P  = .0005) and for pain interference from 62.8 to 56.5 ( P  = .0001). PROMIS depression scores were not significantly different ( P  = .6727). Visual analog scale (VAS) scores significantly decreased from 7.05 to 1.71 ( P  < .0001). Conclusion: In this case series, we found the gastrocnemius recession to be an effective option for patients with refractory pain in plantar fasciitis. Our PROMIS and VAS data confirm this procedure's utility and highlight its ability to significantly decrease pain and improve physical function in patients with chronic plantar fasciitis, although final median scores did not reach normative standards for the population, suggesting some residual pain and/or dysfunction was, on average, present. Based on the results of this study, the authors conclude that gastrocnemius recession is a reasonable treatment option for chronic plantar fasciitis patients who fail nonoperative management. Level of Evidence: Level III, retrospective cohort study.